The association between pulse wave velocity and heart failure: a systematic review and meta-analysis - Esmaeili, Zahra; Bahiraie, Pegah; Vaziri, Zahra; Azarboo, Alireza; Behnoush, Amir Hossein; Khalaji, Amirmohammad; Bazrgar, Aida; Tayebi, Pouya; Ziaie, Naghmeh (Frontiers in Cardiovascular Medicine, 2024)
The arterial stiffness measured by pulsed wave velocity (PWV) is associated with heart failure (HF).However, the effectiveness of arterial stiffness and PWV as prognostic indicators in patients with HFpEF and HFrEF is still unclear. In this systematic review and meta-analysis, we synthesized the prognostic value of PWV and arterial stiffness in HF patients.Four databases, including Embase, PubMed, Scopus, and Web of Science, were systematically searched for published studies assessing the relationship between PWV and HF from inception up to August 31, 2023. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included studies. The standardized mean difference (SMD) and their corresponding 95% confidence intervals (CI) were used to compare PWV in HF (HFrEF and HFpEF) and controls. Meta-regressions based on age, year of publication, sample size, and gender (male percentage) were also conducted.Patients with HF exhibit significantly higher arterial stiffness, as indicated by PWV, compared to the normal population. However, this association was not significant between HFrEF and HFpEF patients.Future research is warranted to establish the potential prognostic role of PWV in HF.